2010
DOI: 10.1007/s00128-010-9983-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Effect of Produced Water on Cod, Gadus morhua, Sperm Cells and Fertilization

Abstract: The in vitro effect of produced water released by oil and gas platforms was assessed by exposing cod sperm cells to realistic concentrations of this mixture (100, 200, 500 ppm). We investigated produced water impact on enzymes of the aerobic (citrate synthase) and glycolytic metabolism (lactate dehydrogenase), lipid catabolism (lipase), as well as an anti-oxidant enzyme (catalase). Fertilization rates, viability, respiration, ATP, and total motility duration were also evaluated. To explore correlations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
7
2
Order By: Relevance
“…Energy levels and enzymes involved in glycolytic metabolism can provide good indices of the general status of sperm; nonetheless, data from the literature show conflicting results when reporting existing correlations with fertilization, and most studies link metabolism with motility rather than with fertilizing capacity (e.g., Perchec et al 1995). Similarly, Hamoutene et al (2010) found no correlations between some of the characteristics explored in this study and no correlations with fertilization rates. Studies on numerous fish species have shown that energy used during sperm motility is made available from ATP that is accumulated before activation (Billard and Cosson 1990;Perchec et al 1995), from ATP that is regenerated during and even after motility (i.e., through respiration and glycolysis), and from lipid catabolism (Billard and Cosson 1990;Lahnsteiner et al 1993;Mansour et al 2003).…”
Section: Resultscontrasting
confidence: 69%
See 3 more Smart Citations
“…Energy levels and enzymes involved in glycolytic metabolism can provide good indices of the general status of sperm; nonetheless, data from the literature show conflicting results when reporting existing correlations with fertilization, and most studies link metabolism with motility rather than with fertilizing capacity (e.g., Perchec et al 1995). Similarly, Hamoutene et al (2010) found no correlations between some of the characteristics explored in this study and no correlations with fertilization rates. Studies on numerous fish species have shown that energy used during sperm motility is made available from ATP that is accumulated before activation (Billard and Cosson 1990;Perchec et al 1995), from ATP that is regenerated during and even after motility (i.e., through respiration and glycolysis), and from lipid catabolism (Billard and Cosson 1990;Lahnsteiner et al 1993;Mansour et al 2003).…”
Section: Resultscontrasting
confidence: 69%
“…Similarly, Hamoutene et al (2010) found no correlations between some of the characteristics explored in this study and no correlations with fertilization rates. Studies on numerous fish species have shown that energy used during sperm motility is made available from ATP that is accumulated before activation (Billard and Cosson 1990;Perchec et al 1995), from ATP that is regenerated during and even after motility (i.e., through respiration and glycolysis), and from lipid catabolism (Billard and Cosson 1990;Lahnsteiner et al 1993;Mansour et al 2003).…”
Section: Resultscontrasting
confidence: 48%
See 2 more Smart Citations
“…Several of these compounds are classified as endocrine-disrupting chemicals, mutagens, and carcinogens, and were found to exert cytotoxic, immunotoxic, mutagenic, and/or carcinogenic effects on a range of different organisms (Evanson & Van Der Kraak, 2001;Hasselberg et al, 2004;Livingstone, 2001;Machala et al, 2001;Santodonato, 1997). Numerous studies have reported physiological and biochemical alterations in aquatic organisms after exposure to PW, or components of PW alone, including DNA damage, micronuclei (MN) formation, oxidative stress, changes in CYP expression, and altered metabolism in germ cells (Caliani et al, 2009;Farmen et al, 2010;Hamoutene et al, 2010;Stephens et al, 2000;Sturve et al, 2006). The most well-studied compounds of PW are polycylic aromatic hydrocarbons and alkyl phenols, which both can cause severe effects on marine wildlife (Aas et al, 2000;Cardinali et al, 2004;Evanson & Van Der Kraak, 2001;Meier et al, 2007;Nicolas, 1999;Schwaiger et al, 2002).…”
Section: Toxicological Effects Of Produced Water and Oil Dischargesmentioning
confidence: 99%